2020
DOI: 10.1097/qai.0000000000002428
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Exposed, Uninfected Infants in Uganda Experience Poorer Growth and Body Composition Trajectories than HIV-Unexposed Infants

Abstract: Background: HIV-uninfected infants of HIV-positive women may experience worse growth and health outcomes than infants of HIV-negative women, but this has not been thoroughly investigated under the WHO's most recent recommendations to reduce vertical transmission.Objective: To determine if HIV-exposed and -uninfected (HEU) infants whose mothers received Option B+ have higher odds of experiencing suboptimal growth trajectories than HIV-unexposed,uninfected infants and if this relationship is affected by food ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
4
8
0
Order By: Relevance
“…In our study, a lower mean LAZ was found in HEU infants at 6 months, which is similar to another South African study [ 58 ], and a lower mean HCZ was also reported in Zimbabwe at 6 months [ 59 ]. A lower mean LAZ was also observed at 9 months in HEU infants as compared to HUU infants, similar to other studies in Uganda [ 60 ], Rwanda [ 61 ], and Botswana [ 10 ]. HEU infants were at a higher risk of being stunted (12.5% vs. 7.1%) at 9 months as compared to HUU infants.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, a lower mean LAZ was found in HEU infants at 6 months, which is similar to another South African study [ 58 ], and a lower mean HCZ was also reported in Zimbabwe at 6 months [ 59 ]. A lower mean LAZ was also observed at 9 months in HEU infants as compared to HUU infants, similar to other studies in Uganda [ 60 ], Rwanda [ 61 ], and Botswana [ 10 ]. HEU infants were at a higher risk of being stunted (12.5% vs. 7.1%) at 9 months as compared to HUU infants.…”
Section: Discussionsupporting
confidence: 89%
“…In a recent systematic review, 14 studies had used some form of growth mixture modelling to investigate BMI trajectories starting at birth and another 49 to investigate BMI trajectories starting at some time after birth 49 . We could only, however, find 7 studies which had investigated latent patterns of early childhood body weight trajectories 18‐24 . In one publication, a growth mixture model was developed using serial weight Z ‐scores (according to the WHO Standards) between 0 and 36 months in 1364 singleton, term infants 22,50 .…”
Section: Commentmentioning
confidence: 99%
“…While simple, easily identifiable traits are unarguably a core and important aspect of growth monitoring, a better understanding of the different patterns of early childhood weight gain that may exist in a population is needed and would be informative for those interested in monitoring the growth of children. Numerous papers have summarised early childhood weight trajectories in terms of individual‐level traits, 5,9‐11 but we are only aware of seven publications that have analysed early childhood weight data using growth mixture modelling, 18‐24 an advanced technique that identifies distinct latent classes of individuals who share similar trajectories 25 . None of these publications included a normal, healthy sample in a high‐income country with body composition outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,8,9 Similar considerations are also possible for the impaired postnatal growth that has been commonly reported in HEU, with variable consistency of findings. 4,[10][11][12][13][14][15][16][17] Comparative studies in the era of universal and lifelong maternal ART therapy, when mortality is expected to be low, 9 are limited. To contribute to this issue, we designed a longitudinal cohort study of mother-infant pairs with different maternal HIV status, followed for 1 year postnatally in three health facilities in Malawi.…”
Section: Introductionmentioning
confidence: 99%